Intestinal SURF4 in dyslipidaemia and female-specific metabolic disorders: insights from rats with polycystic ovary syndrome - Xu, Yating; Si, Yu; Ning, Li; Wang, Ruyue; Ma, Hua; Li, Xiu; Zhao, Hongting; Ren, Qingling (Frontiers in Nutrition, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is a complex endocrine disorder characterized by hyperandrogenism, ovulatory dysfunction, and metabolic disturbances, including dyslipidaemia. Recent studies have suggested that intestinal surfeit locus protein 4 (SURF4) contributes to elevated serum PCSK9 levels and subsequent lipid accumulation, with evidence of sex-specific differences in its expression and regulatory effects. This study aimed to investigate the involvement of intestinal SURF4 in the pathogenesis of PCOS and its potential contribution to metabolic lipid disturbances, as well as to explore lipid-PCOS associations through Mendelian randomization (MR) analysis.MethodsThis research established two rat models of PCOS: one by administering letrozole in combination with a high-fat diet (Model, n = 5) and another by subcutaneous injection of DHEA (DHEA, n = 5). Intestinal SURF4 expression levels were assessed using immunohistochemistry and quantitative polymerase chain reaction. Quantitative serum lipid profiles and androgen levels evaluated the metabolic and hormonal alterations associated with PCOS. Group differences were assessed using ANOVA with post-hoc tests. Mendelian randomization (MR) analyses were conducted to assess the causal relationship between genetic lipid traits and PCOS risk, using data from 10,074 PCOS cases and 103,164 controls.ResultsThe PCOS rat model exhibited significant upregulation of intestinal SURF4 accompanied by dyslipidaemia and elevated androgen levels. Elevated androgen levels may regulate intestinal SURF4 expression, contributing to disturbances in lipid metabolism. MR analyses indicated that PCOS leads to serum lipid abnormalities rather than vice versa.ConclusionThese findings suggest that intestinal SURF4 may serve as a potential intervention target for improving lipid metabolic disorders associated with PCOS.